Fatness and Failing Citizenship. (September 2017) - Rinaldi, Jen; Rice, Carla; LaMarre, Andrea; McPhail, Deborah; Harrison, Elisabeth
Abstract : This article examines how queer persons negotiate the technologies of health deployed to shape sexual citizenship, especially in relation to body size. Beginning with the claim that fatness is always already queered, the authors bring Jasbir Puar's concept of homonationalism into conversation with Samantha Murray's argument that fat persons are positioned as failed citizens. The authors illustrate how fat embodied subjects confront problematics of belonging through analysing in-depth interviews conducted for a research project that investigated how members of queer communities come up against, are affected by and resist body image ideals and body management expectations. Interview excerpts are organised around sites of constraint, contestation and creativity: medical space, queer space and the body as space.